QARAQALPAQ JÍRAWLARÍNDA USTAZ-ShÁKIRT DÁSTÚRI (Qıyas jıraw mısalında) - Yaxiyayeva, Shaxnoza (SCIENCE and SOCIETY, 2026)
The article examines the "master-apprentice" traditions in the Karakalpak art of zhyrau, focusing on the life and creative path of Qiyas zhyrau Kairatdinov. It analyzes the criteria for choosing a mentor, the educational process, and the socio-cultural significance of the "patia" (blessing) ceremony, which is regarded as the pinnacle of becoming a professional storyteller.